The Quality of Human and Non-Human Relation in Indonesia and England Portrayed in the Selected Picture Books - Syahruni Junaid; Ahmad; Nurhidayah; Aan Mujizat; Citra Andini (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study aims 1) to reveal the similarity of  The Tooth Fairies and Cleaning Factory and Kemana Tomat Pergi literary works in ecocritical theory and 2) to reveal how useful the selected picture book in building children’s awareness of the natural environment. This study was talking about the identification of  human or non human-nature relationship and awareness building as reflected in the picture books from Indonesia Kemana Tomat Pergi and from England The Tooth Fairies and Cleaning Factory. This study used a descriptive qualitative method with ecocritical theory, particularly Cheryll Glotfelty's theory and Keraf's supporting theory, to examine how humans and nature relationship are depicted in the two picture books, moreover, the awareness building. The findings of this research indicate that there were two types of relationships between human and nature, consist of good and bad relations. The Indonesian picture book focused on the relationship between Kirin and her tomatoes, while the England picture book focused on the relationship between the little tooth fairy (non-human) and Junior (human) and how humans itself treat nature. Researcher also found from Indonesian picture books that human began to have the awareness after facing struggle in maintaining the balance of nature. meanwhile, the England picture book showed the causes of enormous damage happened in nature. In conclusion, the researcher found that picture books from Indonesia and from England are picture books that are useful in building children’s awareness of the natural environment which is important for life today.